The Credibility of the Information on the Website Pantip.com that Impacts the Decision to Purchase Products Case Study: Beauty Web Board - Homchuangsub, Kamonpan; Tongngam, Sutep (NIDA Development Journal, 2024)
The objectives of this quantitative research were to study the factors related to the credibility assessment of the information on the beauty web board, Pantip.com, with the criteria used to assess the credibility of the information and to study the relationship between the credibility of the information used in the purchase of products and other factors so that users could consider how reliable online information was before deciding to purchase them. The study findings revealed that most of the users were female, with B.A. degrees, occupation student, average income of 10,001 - 20,000 baht, usage of 1 - 2 days, usage of less than one hour, service usage of less than one year, status of irregular customer, and the objective was to follow, read, and seek information only. The factors related to age, education, occupation, and income were related to the criteria used to assess the credibility of the information. In terms of behavior of information usage, it was found that the duration of usage and the length of service were related to the criteria used to assess the credibility of the information. The attitude factor towards the inquirer’s experience and information on the beauty web board, the website Pantip.com, was related to the criteria used to assess the credibility of the information in all aspects which had a high level of relationship. The format factor of the information presentation on the beauty web board, the website Pantip.com, was related to the criteria used to assess the credibility of the information in all aspects which had a high level of relationship, and the criteria used to assess the credibility of the information was related to the purchase of products which had a moderate level of relationship. The results could be useful for both websites and business.